Applications and Efficacy of Iron Oxide Nanoparticles in the Treatment of Brain Tumors - London Varalli; Reed Berlet; EC Abenojar; John McDaid; David A. Gascoigne; Julian Bailes; Daniil P. Aksenov (Pharmaceutics)
Cancers of the central nervous system are particularly difficult to treat due to a variety of factors. Surgical approaches are impeded by the skull—an issue which is compounded by the severity of possible harm that can result from damage to the parenchymal tissue. As a result, chemotherapeutic agents have been the standard of care for brain tumors. While some drugs can be effective on a case-by-case basis, there remains a critical need to improve the efficacy of chemotherapeutic agents for neurological cancers. Recently, advances in iron oxide nanoparticle research have highlighted how their unique properties could be leveraged to address the shortcomings of conventional therapeutics. Iron oxide nanoparticles combine the advantages of good biocompatibility, magnetic susceptibility, and functionalization via a range of coating techniques. Thus, iron oxide nanoparticles could be used in both the imaging of brain cancers with magnetic resonance imaging, as well as acting as trafficking vehicles across the blood–brain barrier for targeted drug delivery. Moreover, their ability to support minimally invasive therapies such as magnetic hyperthermia makes them particularly appealing for neuro-oncological applications, where precision and safety are paramount. In this review, we will outline the application of iron oxide nanoparticles in various clinical settings including imaging and drug delivery paradigms. Importantly, this review presents a novel approach of combining surface engineering and internal magnetic targeting for deep-seated brain tumors, proposing the surgical implantation of internal magnets as a next-generation strategy to overcome the limitations of external magnetic fields.